Transforming Dormitory-Based Arabic Language Learning to Develop Students’ Communicative Competence at Sunan Drajat Islamic Boarding School - Fariha Kustina; Biyati Ahwarumi; Anas Alhifni; Abqoriyah Yumna (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2026)
This study examines the transformation of dormitory-based Arabic language learning in developing students’ communicative competence at Sunan Drajat Islamic Boarding School, Lamongan. It explores the shift from classroom-centered instruction toward environment-based communicative learning through the implementation of bi’ah lughawiyah in dormitory settings. Previous studies have mainly viewed bi’ah lughawiyah as a supporting language environment or examined its impact on specific language skills, with limited attention to its role as an integrated pedagogical system. This study employed a qualitative case study design. Data were collected through moderate participant observation, semi-structured interviews, and document analysis involving students, dormitory supervisors, and Arabic language teachers. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal a pedagogical transformation characterized by the integration of formal instruction, structured bi’ah lughawiyah, intensive social interaction, and the development of students’ communicative competence through sustained input, meaningful interaction, and contextualized language use. The study’s primary contribution is the Integrative Communicative Immersion Model, which extends previous research by conceptualizing dormitory-based Arabic learning as an integrated pedagogical system in which formal instruction, structured language environment, and sustained social interaction function as interconnected components of communicative language acquisition. This model provides a conceptual framework for designing and managing environment-based Arabic language learning in Islamic boarding schools.